Efektivitas Media Sosial Instagram Humas Dispora Provinsi Sumatera Utara Dalam Meningkatkan Citra - Ahyani, Tanthowi Jauhari; Sazali, Hasan; Yoserizal, Yoserizal (Journal of Educational Research and Humaniora (JERH), 2024)
This research aims to find out how effective the use of Instagram social media is i building Disporaprovsu image. The theories used in this research are new media theory, goverment public relations, effectiveness. New media thoery and social media. The subjects of this research are Dispora Public Relations staff who manage Disporaprovsu Instagram and 5 Disporaprovsu Instagram followers. With research dates starting from 03 March 2022 – 27 May 2022. The method used in this reseach is the Qualitative Method with in-depth Interviews. The technical analysis used is descriptive qualitative analysis. The results of this reseacrh show that the effectiveness of Instagram media users is deep The Public Relations image of the North Sumatera Utara Province Dispora is very good, the role of the North Sumatera Province Dispora Public Relations is very good, Plus there are also social media such as Instagram. Making it easier for people to get the latest services and information and news that is currently hot, especially, in the North Sumatera Province area. The dimensions used to measure it’s effectiveness are by conducting interviews using qualitative methods and using new theory media related to research means that the use of Instagram social media by Public Relations of Dispora @Disporasumut.id as a medium for disseminating information to the public is effective The Public Relations Division as manager of @Disporasumut.id can be said quality photos and videos. So the goal of improving the image thourgh the use of Instagram social media was achieved.